The Impact of Artificial Intelligence on Organizational Efficiency and Innovation - Malik, Sushma; Rana, Anamika (Journal of Graphic Era University, 2025)
Artificial Intelligence (AI) is increasingly reshaping the landscape of modern organizations, driving significant improvements in operational efficiency and fostering innovation across various sectors. This paper explores the transformative role of AI technologies, such as machine learning, natural language processing, and robotic process automation, in enhancing productivity and streamlining workflows. By automating routine tasks, AI reduces human error and frees up valuable resources, allowing employees to focus on higher-level strategic initiatives. Furthermore, the integration of AI facilitates data-driven decision-making, enabling organizations to glean actionable insights from vast datasets. This capability not only enhances operational efficiency but also promotes a culture of innovation by empowering teams to experiment with new ideas and approaches. The paper highlights case studies across different industries, illustrating how AI applications have led to significant advancements in product development, customer service, and process optimization.